Evaluation of perinatal arterial ischemic stroke patients: A single center experience - Koçak, Ozan (Journal of Surgery and Medicine, 2020)
Aim: Perinatal arterial ischemic stroke (PAIS) is the one of the frequent causes of morbidity and neurologic disability, such as unilateral cerebral palsy (UCP), epilepsy and neurodevelopmental deficiencies. The aim of this study is to determine the clinical characteristics, risk factors and long term outcomes of PAIS patients. Methods: This retrospective cohort study was conducted with 49 PAIS patients who were followed up in the Pediatric Neurology Department between January 2009 and September 2015. Clinical data including demographic features, gestational history, age at diagnosis, initial clinical presentation, brain MRI features, perinatal risk factors and long-term outcome were collected from patient files. Results: The study group comprised 30 females and 19 males with a mean age of 6.3 (4.5) years. Twin pregnancy (6.1%), intrauterine growth retardation (IUGR) (8.2%), peripartum asphyxia (8.2%) and presentation abnormality (6.1%) were the most common maternal / neonatal risk factors. The most common prothrombotic risk factors were MTHFR mutations (42.85%), followed by FVL mutations (16.32%). The epilepsy rate was 73.3%, 6.4% of which had refractory epilepsy. All patients had UCP. Conclusions: Risk factors and their roles in development of PAIS have not been fully established. According to this study, most of the PAIS patients have at least one or more maternal, neonatal or prothrombotic risk factors, and all patients have motor and cognitive impairment related with PAIS. Multi-center prospective studies with more cases are needed to fully enlighten the causes of this disease and to develop preventive measures.